A Shrine to Moses: A reappraisal of the Mount Nebo Monastic Complex between Byzantium and Islam - Bianchi, Davide (Verlag der Österreichischen Akademie der Wissenschaften, 2021)
This book offers new insights into the Memorial of Moses on Mount Nebo, one of the most renowned coenobitic monasteries in the Byzantine period in Arabia. Starting from the archaeological data, the author critically reflects on the architectural phases of the basilica, the management and daily life in the monastery. Special attention is also given to pilgrimages to the monastic shrines beyond the River Jordan and their progressive abandonment.